2018
DOI: 10.1016/j.anireprosci.2018.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of sperm head dimensions and chromatin integrity of epididymal sperm from domestic cats using the toluidine blue technique

Abstract: When using assisted reproductive technologies, there is seldom an evaluation of DNA integrity during sperm analysis, which is an important variable for proper embryo development. The toluidine blue staining technique allows the simultaneous evaluation of sperm chromatin and sperm head dimensions. The objectives of this study were to evaluate the applicability of the toluidine blue staining method for analyzing DNA abnormalities in epididymal sperm (from the caput, corpus, and cauda) of cats and to investigate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 36 publications
0
4
2
1
Order By: Relevance
“…The sperm abnormalities found in the present study included doubleheader with the coiled tail, bent neck, double tail, macrocephalic with double tail, microcephalic, elongated head, and hairpin tail. The sperm abnormalities in this study were higher when compared with the normal value reported by Alves et al (2018). Alves et al (2018) reported that the normal value of cat sperm abnormalities was about 16.7 ± 9.9%.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…The sperm abnormalities found in the present study included doubleheader with the coiled tail, bent neck, double tail, macrocephalic with double tail, microcephalic, elongated head, and hairpin tail. The sperm abnormalities in this study were higher when compared with the normal value reported by Alves et al (2018). Alves et al (2018) reported that the normal value of cat sperm abnormalities was about 16.7 ± 9.9%.…”
Section: Discussioncontrasting
confidence: 67%
“…The sperm abnormalities in this study were higher when compared with the normal value reported by Alves et al (2018). Alves et al (2018) reported that the normal value of cat sperm abnormalities was about 16.7 ± 9.9%.…”
Section: Discussioncontrasting
confidence: 67%
“…Two hundred spermatozoa per smear were examined under a light microscope by two embryologists at ×100 magnification. The cells were classified into two groups: TB positive cells (TB+) (dark violet cells; altered chromatin) and TB negative cells (TB−) (light blue cells; normal chromatin structure) (Tsarev et al ., 2009; Alves et al ., 2018).…”
Section: Methodsmentioning
confidence: 99%
“…In a study conducted on sperm collected from feline epididymides, smaller dimensions of sperm heads in the epididymal cauda were found than in the caput and corpus [23]. The study of these authors also found that the sperm head dimension was correlated with chromatin decondensation, and the sperm head size decreased as the sperm were trans-ported through the three epididymal regions.…”
Section: Discussionmentioning
confidence: 94%